Impact of digital media on language revitalization: the case of BBC News Igbo - Eke, Ikechukwu Williams; Salawu, Abiodun (Frontiers in Communication, 2026)
The United Nations Educational, Scientific, and Cultural Organization (UNESCO) has identified the Igbo language as critically threatened. The language has low linguistic and social profiles, which make it unappealing to producers and advertisers and limit its access to the mass media. Given the growing effectiveness of digital media to revitalize threatened languages, this research examines the impact a new media platform might have on Igbo language revitalization. The study adopts a mixed methods approach to specifically explore the extent to which BBC News Igbo has enriched the prestige of the Igbo language. These findings indicated that the medium has significantly enhanced the linguistic and social values of the language through restoration of pride, digitization, revival of interest, global access and visibility, attitudinal shift, domain expansion, and social media presence. The cumulative impact of the findings on the Igbo language is confidence in its greater use, which is renowned for abetting the revitalization of endangered languages.